Developing ESP Reading Materials by using Authentic Materials for Automotive Students at SMKN 2 Jember - Frieda Puspita K.D; I Putu Sukmaantara; Asih Santihastuti (Pendidikan Fisika FKIP UNEJ, 2017)
Abstract: This research and development was intended to develop ESP reading materials for automotive students by using authentic materials at SMKN 2 Jember. This research used Research and Development (R&D) as the research design which consisted of conducting needs analysis, developing ESP Reading materials, conducting validation, doing revision, administering try out, and finalising the materials adapted by Gall et al., The research subject of this research were automotive students at SMK Negeri 2 Jember. The data was collected by interviewing the English Teacher and giving questionnaires to the students. Based on the result of interviewing the English teacher, it was found that the teacher taught general English like in Senior High School for Vocational students. Actually the vocational students needs English in specific purpose. ESP reading materials can help the students to face their future job. They can understand about their manual books written in English. . After the students learnt about ESP Reading Materials, they felt happy because they learnt English related to their major. The result of this research was the ESP Reading materials for automotive students in the form of booklet. Keywords: ESP, Material Development, Research and Development, Reding Materials, Authentic Materials